2018
DOI: 10.1128/aac.00009-18
|View full text |Cite
|
Sign up to set email alerts
|

Potent Activities of Luliconazole, Lanoconazole, and Eight Comparators against Molecularly Characterized Fusarium Species

Abstract: A collection of clinical ( = 47) and environmental ( = 79) isolates were tested against 10 antifungal drugs, including 2 novel imidazoles. Luliconazole and lanoconazole demonstrated very low geometric mean MIC values of 0.005 and 0.013 μg/ml, respectively, compared with 0.51 μg/ml for micafungin, 0.85 μg/ml for efinaconazole, 1.12 μg/ml for natamycin, 1.18 μg/ml for anidulafungin, 1.31 μg/ml for voriconazole, 1.35 μg/ml for caspofungin, 1.9 μg/ml for amphotericin B, and 4.08 μg/ml for itraconazole. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
8
28
1
Order By: Relevance
“…34 Similarly, in this study, E483K and P486S substitutions located close to access channel are suggested to behave the same way as L98H substitution of CYP51A of A. fumigatus. In contrast, similar to several previous reports, [35][36][37][38][39] antifungal activity of new imidazoles, luliconazole and lanoconazole, against all A. clavatus isolates was surprisingly superior to amphotericin B, triazoles, caspofungin, and allylamines, suggesting promising candidates for the treatment of different forms of cutaneous aspergillosis caused by this species.…”
supporting
confidence: 88%
“…34 Similarly, in this study, E483K and P486S substitutions located close to access channel are suggested to behave the same way as L98H substitution of CYP51A of A. fumigatus. In contrast, similar to several previous reports, [35][36][37][38][39] antifungal activity of new imidazoles, luliconazole and lanoconazole, against all A. clavatus isolates was surprisingly superior to amphotericin B, triazoles, caspofungin, and allylamines, suggesting promising candidates for the treatment of different forms of cutaneous aspergillosis caused by this species.…”
supporting
confidence: 88%
“…With the exception of a single isolate of F. verticillioides which had an MIC of 8 g/ml, all had MICs of 16 g/ml (Table 1). These results concur with previously published data on azoles versus Fusarium sp., with MICs of Ն8 for itraconazole (31,32). In conclusion, we found that the in vitro antifungal activity of tavaborole against a panel of different agents of onychomycosis is inferior to those of terbinafine and azoles, except for fluconazole.…”
mentioning
confidence: 60%
“…All these emerging strains exhibited susceptibility to antifungal drugs, except for A. sydowii , which was inhibited at the concentration of ≥1 μg/mL of efinaconazole and allylamines. On the other hand, our MIC results of two novel imidazoles, namely luliconazole and lanoconazole, against all Aspergillus strains, even against the emerging species, remarkably showed low MIC values of these agents, compared to those of the common antifungal drugs …”
Section: Discussionmentioning
confidence: 84%
“…Fusarium species identification was confirmed by ITS rDNA region and partial sequencing of the translation elongation factor‐1 alpha (TEF ‐1 α) …”
Section: Methodsmentioning
confidence: 99%